Influence of Software Tool and Methodological Aspects of Total Metabolic Tumor Volume Calculation on Baseline [18F]FDG PET to Predict Survival in Hodgkin Lymphoma - Kanoun, Salim (PLoS One, 2015)
AIM: To investigate the respective influence of software tool and total metabolic tumor volume (TMTV0) calculation method on prognostic stratification of baseline 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography ([18F]FDG-PET) in newly diagnosed Hodgkin lymphoma (HL). METHODS: 59 patients with newly diagnosed HL were retrospectively included. [18F]FDG-PET was performed before any treatment. Four sets of TMTV0 were calculated with Beth Israel (BI) software: based on an absolute threshold selecting voxel with standardized uptake value (SUV) >2.5 (TMTV0(2.5)), applying a per-lesion threshold of 41% of the SUV(max) (TMTV0(41)) and using a per-patient adapted threshold based on SUV(max) of the liver (>125% and >140% of SUV(max) of the liver background; TMTV0(125) and TMTV0(140)). TMTV0(41) was also determined with commercial software for comparison of software tools. ROC curves were used to determine the optimal threshold for each TMTV0 to predict treatment failure. RESULTS: Median follow-up was 39 months. There was an excellent correlation between TMTV0(41) determined with BI and with the commercial software (r = 0.96, p<0.0001). The median TMTV0 value for TMTV0(41), TMTV0(2.5), TMTV0(125) and TMTV0(140) were respectively 160 (used as reference), 210 ([28;154] p = 0.005), 183 ([-4;114] p = 0.06) and 143ml ([-58;64] p = 0.9). The respective optimal TMTV0 threshold and area under curve (AUC) for prediction of progression free survival (PFS) were respectively: 313ml and 0.70, 432ml and 0.68, 450ml and 0.68, 330ml and 0.68. There was no significant difference between ROC curves. High TMTV0 value was predictive of poor PFS in all methodologies: 4-years PFS was 83% vs 42% (p = 0.006) for TMTV0(2.5,) 83% vs 41% (p = 0.003) for TMTV0(41,) 85% vs 40% (p<0.001) for TMTV0(125) and 83% vs 42% (p = 0.004) for TMTV0(140). CONCLUSION: In newly diagnosed HL, baseline metabolic tumor volume values were significantly influenced by the choice of the method used for determination of volume. However, no significant differences were found in term of prognosis.